Taxonomic peculiarities of marcescent oaks (Quercus, Fagaceae) In southern Portugal - Vila-Viçosa, Carlos Magno; Vázquez, Francisco M.; Meireles, Catarina; Pinto-Gómes, Carlos (Lazaroa, 2014)
geobotanical studies on marcescent groves in southern Portugal have led to a clarification and updating of the taxonomical status of some Quercus species, after ambiguous and specific collections recorded through extensive fieldwork. We highlight the situation of Q. canariensis Willd. in Portugal, mainly referring to the hybrid-species Q. xmarianica C.Vicioso, whose new status is proposed here. We also confirm and discuss the occurrence of two dubious taxa (Q. alpestris Boiss. and Q. estremadurensis O. Schwarz) for Portuguese flora that are not listed or recognized in the main works, and we note some nomenclatural issues for the first (Q. alpestris). Likewise, reference is made to another two nothospecies resulting from hybridization that have recently been recognized in this context, in addition to another four hybrids that arealready known but still unfamiliar to the scientific community due to the controversial issue of hybridization within thisgenus. This study reveals the importance of taxonomical surveys for community ecology.